PREVALENSI URINARY SYMPTOMS PADA LANSIA - Suryanti, Suryanti; Sulistyowati, Dwi (Medical Journal of Nusantara, 2023)
Background: The aging process causes health problems in the elderly, including urinary system disorders. Urinary symptoms in the elderly are caused by decreased bladder function and decreased muscle tone around the urinary tract. Bladder sphincter effect or neurological dysfunction that causes loss of control over urination. Research objective: to determine the prevalence of Urinary Symptoms in the elderly. Research Method: analytical observational research with a cross sectional approach. Data collection was carried out using a questionnaire. Respondents were all elderly people who lived in the DPK Nursing Home. The instrument used is the International Consultant Incontinence Questionnaire-Urine Incontinence Short Form (ICIQ-UISF) using a diagnostic measuring tool for Urinary Symptoms, which is the ICIQ-UISF questionnaire which consists of 3 questions and has a total score of 21. Urinary Symptoms Score: 0-7, Urinary Symptoms score 8-14, Urinary Symptoms score: score 15-21. The analysis test used is with the help of the SPSS program. Research results: Residents of the DBK Surakarta Nursing Home based on the level of incontinence and female gender, the level of mild incontinence was 9 out of 31 respondents (29%), moderate was 15 out of 31 respondents (48%) and severe was 7 out of 31 respondents (23%). This is because with increasing age or the aging process, the urinary muscles will weaken and bladder capacity will decrease, and this is also supported by a weakening of the anal sphincter. Conclusions and Suggestions: The majority of elderly people in the DPK Nursing Home experience moderate levels of incontinence, so nurses and nursing home staff are expected to carry out further research, for example by providing interventions that can strengthen the pelvic muscles and strengthen the anal sphincter.